(untitled) (Journal of the College of Basic Education, 2022)
In this work, a theoretical comparison was made for the dynamical behavior of the bulk and SQW GaAs/AlGaAs lasers, in which the peak modal gain and threshold current density are studied with varying the active region thickness d=(0.02to 0.3)μm at two reflectivities of (R=0.32 and0.8) and the well widths Lz=(200, 150, 100, and 75) Ǻ for the SQW laser, both at a bandgap discontinuity of ΔEc of 0.1 eV and at a temperature of T=300oK